Nonimmune hydrops fetalis and bilateral pulmonary hypoplasia in a newborn infant with nuchal vascular hamartoma - Özkan, Hasan; Gülen, Hüseyin; Demir, Namık; Özer, Erdener; Haberal, Şebnem; Erçal, Derya; Çevik, Necla T. (The Turkish Journal of Pediatrics, 1997)
Nuchal vascular hamartoma was found in a newborn premature infant who presented with nonimmune hydrops fetalis, pulmonary hypoplasia due to bilateral pleural effusion and polyhydramnios in utero. The baby died 26 hours after birth despite maximal respiratory and circulatory support. Postmortem examination revealed a vascular hamartoma localized to the left posterolateral region of the neck. We suggest that nuchal vascular hamartoma may be associated with fetal hydrops, probably due to compromised lymph drainage.